Escola de referência em ensino médio: uma análise de impacto do programa de ensino integral em Pernambuco - Silva, Rony Ramos Cavalcanti da (2022)
The policy of integral education has been implemented in several regions of the world. The main objective is to extend the school day so that students are more exposed to school activities, in order to improve their academic performance. This paper aims to estimate the effect of the comprehensive school program in Pernambuco on the performance of these schools in the National High School Exam, ENEM, and on school performance rates (failure and dropout). For this, a difference-in-differences model with multiple periods is used, proposed by Callaway and Sant'Anna (2020), because it is a gradually implemented program and, once treated, the school continues to receive the treatment throughout the observation period. The results show an average reduction of around 2 percentage points in the dropout and failure rates; however, despite being positive, the effect of the program on the ENEM was modest, where the greatest impact was 3.5% in mathematics.